2007
DOI: 10.1117/12.730948
|View full text |Cite
|
Sign up to set email alerts
|

Experiment research on orthogonal tilting scanner

Abstract: The original scanner of tilting orthogonal double prisms is studied for testing the tracking performance in inter-satellite laser communications. Two prisms respectively rotate around the horizontal axle and the vertical one within the admissible range to determine the corresponding orientation and position of the passing beam, therefore the high accuracy deviation angle of passing beam can be performed. The test experiments performed with autocollimator and interferometer, as well as the theoretical analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…During the past work, pharmacological and clinical research was focused on its alkaloids, oxymatrine, and matrine, because the two alkaloids were considered primarily effective components that are well‐known target markers of radix S. tonkinensis . They have been found to have anti‐inflammatory , anti‐cancer , and antipyretic functions as well as hepatoprotective effects . Radix S. tonkinensis extract has pharmacological activity, but it also causes toxicities .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past work, pharmacological and clinical research was focused on its alkaloids, oxymatrine, and matrine, because the two alkaloids were considered primarily effective components that are well‐known target markers of radix S. tonkinensis . They have been found to have anti‐inflammatory , anti‐cancer , and antipyretic functions as well as hepatoprotective effects . Radix S. tonkinensis extract has pharmacological activity, but it also causes toxicities .…”
Section: Introductionmentioning
confidence: 99%
“…They have been found to have anti‐inflammatory , anti‐cancer , and antipyretic functions as well as hepatoprotective effects . Radix S. tonkinensis extract has pharmacological activity, but it also causes toxicities . It was reported that oxymatrine and matrine are toxic alkaloids , and the nervous system is the main target organ of the toxicity of matrine .…”
Section: Introductionmentioning
confidence: 99%